Remission of Cognitive Deficits in Parkinson’s Disease: Recovery from a Nonamnestic Mild Cognitive Impairment or Psychiatric Symptoms Remission? - de Paula, Jonas Jardim; Cintra, Marco Túlio Gualberto; Miranda, Débora Marques; Bicalho, Maria Aparecida Camargos; Moares, Edgar Nunes; Malloy-Diniz, Leandro Fernandes (Case Reports in Psychiatry, 2012)
Mild cognitive impairment is a clinical condition more frequent in patients with Parkinson's disease than in general population. The nonamnestic presentations, usually characterized by executive dysfunction, are most prevalent. We present a case report of a Parkinson’s disease patient diagnosed with nonamnestic mild cognitive impairment that showed complete remission of cognitive symptoms after one year. We discuss the possible causes for the remission, focusing on the treatment of medical conditions such as a major depressive episode and vitamin B12 deficiency, in addition to the change of pharmacological treatment. In a third assessment, cognitive performance remained normal. The case report highlights the importance of controlling clinical comorbidities on the assessment and followup of mild cognitive impairment, especially on Parkinson’s disease.